Bitcoin dalam Perspektif Geopolitik: Peluang dan Tantangan Adopsi Kripto bagi Kepentingan Nasional Indonesia (Studi Kasus Danantara) - Zamzami, Naufal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze the potential adoption of Bitcoin as a geopolitical instrument in support of Indonesia’s national interests, with a case study on Archipelago’s Daya Anagatha PT (Danantara). The research method adopted was qualitative descriptive-analytical with a global political diplomacy approach. Data were collected through interviews with key informants as well as a study of literature related to regulation, policy, and global dynamics regarding crypto assets. The research results show that Bitcoin has a strategic potential to reduce Indonesia’s dependence on the U.S. dollar, enhance the competitiveness of the digital economy, and strengthen Indonesia’s position in the global financial system. However, its implementation still faces significant challenges, including immature regulations, price volatility, technology infrastructure limitations, and geopolitical risks. Based on the findings, the study recommends strengthening national regulation, enhancing technological and human resource capacities, as well as crypto-based economic diplomacy strategies. Thus, Indonesia can more optimally utilize the opportunities of Bitcoin adoption to support economic self-sufficiency and national interests.